Environmental governance in the european union: a comparative approach with special reference to Turkey - Balcı, Hüma (My University, 2006)
Çevre son zamanlarda ülkelerin ajandalarında ilk sıralarda yer almaya başlamıştır. Bunun temel sebebi çevre sorunsalının boyutlarının canlıların yaşamını tehtid eder hale gelmesidir. Bu durum uluslar arası düzeyde çözüm arayışlarını gerektirmektedir ve çevre yönetişimi fikrini doğurmaktadır. Bu çalışma, Avrupa Birliği’nin çevre yönetişiminin küresel düzeydeki yönetişime bir örnek teşkil edip edemeyeceğini araştırmayı hedeflemektedir. Bu karşılaştırma yapılırken küresel düzeydeki girişimlere Amerika örnek alınmıştır. Bunun sebebi ekonomik ve politik gücüyle Amerika’nın etkinliğinin küresel alanda hissedilmesidir. Karşılaştırmalar yapılırken Türkiye’de Avrupa Birliği’ne üyeliğe aday bir ülke olarak bu konudaki tarihsel geçmişi tartışılarak yer almıştır.

The aim of this thesis is to assess whether the European Union is an efficient regional example to the global environmental governance in which the USA is a powerful actor. It is not only an attempt to analyze the European environmental governance and policies but also an attempt to combine the socio cultural, technological, economical, and legal approaches towards environmental protection all around the world. In this thesis, the multidisciplinary analysis, especially on raising environmental awareness at the grass root level, improvement of the environmental legislation, environmental economics, and the environmental responsibilities are also discussed on a wider scale. In this point, EU initiates unique policies to control the market related failures. Consequently, the importance of the USA as powerful environmental actor is taken into consideration in terms of Transatlantic environmental relations and finally, Turkey is examined as a case study by giving importance to the environmental participation, education, and institutionalization with regard to EU Turkey accession partnership.
Keywords: Avrupa Birliği_Türkiye; Çevre Politikası_Avrupa Birliği; Çevre Sorunları_Türkiye